Institutional Deadlock and Strategic Execution of Islamic Banking Disputes in Indonesia: A Post-Constitutional Court Decision No. 93/PUU-X/2012 Juridical-Financial Analysis - Rachmad Risqy Kurniawan (International Journal of Economic and Business Research, 2026)
Constitutional Court Decision No. 93/PUU-X/2012 promotes an epistemological reconstruction of Sharia economic jurisdiction by affirming the absolute jurisdiction of the Religious Courts. However, this integration faces systemic obstacles when it intersects with the acceleration of corporate actions, such as mergers and spin-offs, which leave administrative residues on collateral assets. This study aims to analyze the dissonance between jurisdictional certainty, judicial digitization, and the rigidity of administrative bureaucracy in the execution of collateral following the consolidation of Islamic banking. The method employed is normative legal research using an interdisciplinary approach through Institutional Theory and the Efficiency Structure Hypothesis (ESH). The analysis focuses on the friction between formal rules and informal constraints in handling legacy assets. The results reveal a “Digitalization Paradox,” wherein the efficiency of e-litigation does not align with the effectiveness of physical enforcement. The primary issue lies in the institutional rigidity of agencies such as the National Land Agency (BPN) and the National Property Management Agency (KPKNL) in enforcing assets due to discrepancies in creditor identities. Debtors exploit this gap through third-party objections to delay auctions. Consequently, transaction costs rise, disrupting the efficiency and liquidity stability of Islamic banking. Therefore, regulatory synchronization and strengthened governance are necessary to ensure legal certainty and system efficiency.